Effect of pd and dd reactions enhancement in deuterides TiD2, ZrD2 and Ta2D in the astrophysical energy range; Physics of Particles and Nuclei Letters; Vol. 13, iss. 1 - Bystritsky V. M. Vyacheslav Mikhaylovich; Dudkin G. N. Gennadiy Nikolaevich; Filipovich M. Marius; Guran Ye. Yezhek; Krylov A. R. Aleksandr Romanovich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Penkov F. M. Fedor Mikhaylovich; Filippov A. V. Andrey Vladimirovich; Tuleushev Yu. Zh. Yury Zhianshakhovich (Physics Of Elementary Particles And Atomic Nuclei. Experiment, 2016)
Title screen